The Mitochondrial Translocator Protein and the Emerging Link Between Oxidative Stress and Arrhythmias in the Diabetic Heart - Ilkan, Zeki; Akar, Fadi G. (Frontiers in Physiology, 2018)
Mitochondrial dysfunction is a hallmark of common metabolic diseases, such as obesity and diabetes mellitus. While the role of the mitochondrial network in regulating cardiac energy production and cell death pathways is well-established, its active control of other critical functions, including myocardial excitability and arrhythmias is far less understood. In this review article, we highlight the emerging mechanistic links between mitochondrial dysfunction, oxidative stress, and arrhythmogenesis in the diabetic heart. A comprehensive analysis of all the factors by which defective mitochondrial bioenergetics and altered cellular redox status can affect ion channel function in diabetes is well outside the scope of a single review article. Therefore, here we focus on a central mechanism of arrhythmogenesis that is regulated by a key mitochondrial outer membrane protein known as the translocator protein (TSPO). We begin by describing the discovery and the molecular identity of TSPO, and its various roles in the mitochondrion especially as a mediator of oxidative stress. This is then followed by an analysis of how dynamic mitochondrial instability can arise from the systematic amplification of reactive oxygen species (ROS) through a regenerative process known as ROS-induced ROS release (RIRR), culminating in electrical instability at the cellular and intact heart levels. We then then provide a summary of the recent studies which describe the relevance of TSPO to the pathophysiology of diabetes, where the balance between ROS production and ROS scavenging is disrupted in favor of oxidative stress.